2007
DOI: 10.4067/s0717-95022007000400032
|View full text |Cite
|
Sign up to set email alerts
|

The Accessory Soleus Muscle: Case Report and a Review of the Literature

Abstract: SUMMARY: An accessory soleus muscle was found in the left leg of a male cadaver in the dissecting room. The muscle was situaded posteromedially, between the soleus muscle and the flexor digitorum longus and flexor hallucis longus. The origin of the muscle was in the superior third of the anterior fascia of the soleus muscle and the insertion, was attached with separate tendon, in the anteromedial surface of calcaneus bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This result corroborates some studies reporting ASM as present in up to 10% of humans (9,14,15) . Moreover, most reports in the literature stated a 0.7 to 5.5% presence of ASM in human beings (2,3,5,11,13,(16)(17)(18)(19) . Some investigators reported a prevalence ranging from 1 to 6% in human beings (6,20) .…”
Section: Discussionmentioning
confidence: 99%
“…This result corroborates some studies reporting ASM as present in up to 10% of humans (9,14,15) . Moreover, most reports in the literature stated a 0.7 to 5.5% presence of ASM in human beings (2,3,5,11,13,(16)(17)(18)(19) . Some investigators reported a prevalence ranging from 1 to 6% in human beings (6,20) .…”
Section: Discussionmentioning
confidence: 99%
“…g. Accessory soleus muscle: This is a rare congenital anomaly is located anterior to the soleus. 182 It is estimated to be present in 0.7 to 5.5% of the population but only 70 symptomatic cases have been reported between 1965 and 1996 and 100 cases from 1869 to 1995. 182 Reported symptoms often include pain and soft tissue swelling in the medial aspect of the distal lower leg that increases with exercise and relieves with rest.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…182 It is estimated to be present in 0.7 to 5.5% of the population but only 70 symptomatic cases have been reported between 1965 and 1996 and 100 cases from 1869 to 1995. 182 Reported symptoms often include pain and soft tissue swelling in the medial aspect of the distal lower leg that increases with exercise and relieves with rest. 182 Reported cases have also presented with symptoms similar to compartment syndrome.…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations